∫ 0 π / 2 ( cos 3 θ + sin 3 θ ) 2 / 3 d θ = Γ 3 ( c / d ) a π 2 / b
The equation above holds true for positive integers a , b , c , and d , where g cd ( a , b ) = g cd ( c , d ) = 1 and c is minimized. Find 1 0 0 0 a + 1 0 0 b + 1 0 c + d .
Notation: Γ ( ⋅ ) denotes the gamma function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that the answer is not unique. Since Γ ( 3 2 ) = 2 3 Γ ( 3 5 ) , we can also express the answer as 8 2 7 Γ 3 ( 3 5 ) 9 4 π 2 = Γ 3 ( 3 5 ) 2 4 3 3 2 π 2 .
Log in to reply
Thanks for pointing it out! I have adjusted the problem accordingly.
Problem Loading...
Note Loading...
Set Loading...
Let the given integral be I . Make a substitution ( x = tan 3 θ , d x = 3 tan 2 θ sec 2 θ d θ ) as follows: I = ∫ 0 π / 2 ( ( cos 3 θ + sin 3 θ ) 2 / 3 d θ ) = ∫ 0 π / 2 ( ( cos 3 θ ⋅ ( 1 + tan 3 θ ) ) 2 / 3 d θ ) = ∫ 0 π / 2 ( ( 1 + tan 3 θ ) 2 / 3 sec 2 θ d θ ) = 3 1 ∫ 0 π / 2 ( ( tan 3 θ ⋅ ( 1 + tan 3 θ ) ) 2 / 3 3 tan 2 θ sec 2 θ d θ ) = 3 1 ∫ 0 ∞ ( ( x ( 1 + x ) ) 2 / 3 d x ) Now make the substitution ( x = 1 − u u , d x = ( 1 − u ) 2 d u ): I = 3 1 ∫ 0 ∞ ( ( x ( 1 + x ) ) 2 / 3 d x ) = 3 1 ∫ 0 1 ⎝ ⎛ ( ( 1 − u u ) ( 1 + ( 1 − u u ) ) ) 2 / 3 ( 1 − u ) 2 d u ⎠ ⎞ = 3 1 ∫ 0 1 ( ( u ( 1 − u ) ) 2 / 3 d u ) = 3 1 ∫ 0 1 ( u − 2 / 3 ( 1 − u ) − 2 / 3 d u ) = 3 1 B ( 3 1 , 3 1 ) = 3 1 ⋅ Γ ( 3 2 ) Γ 2 ( 3 1 ) Finally, we use Euler's reflection formula Γ ( z ) Γ ( 1 − z ) = sin ( π z ) π to bring the answer to the desired form: I = 3 1 ⋅ Γ ( 3 2 ) Γ 2 ( 3 1 ) = 3 1 ⋅ Γ 3 ( 3 2 ) ( sin ( π / 3 ) π ) 2 = 3 1 ⋅ Γ 3 ( 3 2 ) 4 π 2 / 3 = Γ 3 ( 2 / 3 ) 4 π 2 / 9 and the answer is 1 0 0 0 ⋅ 4 + 1 0 0 ⋅ 9 + 1 0 ⋅ 2 + 3 = 4 9 2 3 .